UiTM Art Gallery information retrieval based on synonym text / Noor Hafizah Mohd Zain - Mohd Zain, Noor Hafizah (2010)
Information Retrieval is fast becoming the dominant form of information access over taking traditional database style searching. Nowadays, retrieval system is very important in order to search something especially to search in the large database. The use of semantic information into text retrieval or text classification has been controversial. Information Retrieval based on synonym is needed in order to increase the effectiveness of searching system. The objectives of this project are to develop an online search prototype for UiTM Art Gallery with synonym retrieval capabilities. The scope of this project is information of artwork produced by Fine Art department of Faculty Art and Design. This project is implemented using content-based technique for retrieval process. In the future, this project needs enhancement to produce better result with implementing advance stemming and retrieval techniques.